Development and Validation of Work Readiness Assessment Tool for Home Economics Graduates - Wendell Cabrera (Yayasan Riset dan Pengembangan Intelektual, 2020)
This paper focused on the development and validation of a Work Readiness Assessment Scale (WRAS) for Home Economics graduates in Senior High School. It is aimed that the output be used by both the academe and industry in evaluating the work readiness of graduates. Furthermore, it identified the attributes and characteristics of work readiness as basis for scale development through a series of focus group discussions. Four dimensions were identified using NVivo software. The developed WRAS consisting of 15-items per dimension was validated in a sample of 311 Senior High School students using the Rasch Modelling. The results showed unidimensionality; a well-functioning response option; the difficulty of items increases as response option increases; it indicates a productive measure; items are well-structured; and each item can highly discriminate well between test takers with high and low level of work readiness. A correlation study was conducted between the results of the WRAS and Work Immersion grades to validate its functionality.